Polaronic Contributions to Friction in a Manganite Thin Film. Issue 8 (18th February 2021) - Weber, Niklas A.; Schmidt, Hendrik; Sievert, Tim; Jooss, Christian; Güthoff, Friedrich; Moshneaga, Vasily; Samwer, Konrad; Krüger, Matthias; Volkert, Cynthia A.
Abstract: Despite the huge importance of friction in regulating movement in all natural and technological processes, the mechanisms underlying dissipation at a sliding contact are still a matter of debate. Attempts to explain the dependence of measured frictional losses at nanoscale contacts on the electronic degrees of freedom of the surrounding materials have so far been controversial. Here, it is proposed that friction can be explained by considering the damping of stick‐slip pulses in a sliding contact. Based on friction force microscopy studies of La(1− x ) Sr x MnO3 films at the ferromagnetic‐metallic to a paramagnetic‐polaronic conductor phase transition, it is confirmed that the sliding contact generates thermally‐activated slip pulses in the nanoscale contact, and argued that these are damped by direct coupling into the phonon bath. Electron‐phonon coupling leads to the formation of Jahn–Teller polarons and to a clear increase in friction in the high‐temperature phase. There is neither evidence for direct electronic drag on the atomic force microscope tip nor any indication of contributions from electrostatic forces. This intuitive scenario, that friction is governed by the damping of surface vibrational excitations, provides a basis for reconciling controversies in literature studies as well as suggesting possible tactics for controlling friction. Abstract : Friction can be controlled at a manganite surface using the phase transition between the metallic and polaron conductor phases. The sliding tip generates stick‐slip pulses in the contact interface, which are more effectively damped in the polaron conductor phase due to strong electron‐phonon coupling.